2017
DOI: 10.1377/hlthaff.2017.0218
|View full text |Cite
|
Sign up to set email alerts
|

The Uninsured Do Not Use The Emergency Department More—They Use Other Care Less

Abstract: There is a popular perception that insurance coverage will reduce overuse of the emergency department (ED). Both opponents and advocates of expanding insurance coverage under the Affordable Care Act (ACA) have made statements to the effect that EDs have been jammed with the uninsured and that paying for the uninsured population’s emergency care has burdened the health care system as a result of the expense of that care. It has therefore been surprising to many to encounter evidence that insurance coverage incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 26 publications
0
49
1
Order By: Relevance
“…Controlling for sociodemographic and health statuses, those who lacked HI were seven times more likely to have postponed or foregone needed healthcare due to cost, and only 15% to 23% as likely to have had contact with any healthcare professional in the preceding 12 months. We also found that the uninsured aged 50-64 were less likely to have visited an ED than those with public HI; however, in contrast to an aforementioned earlier study finding [22], we found no difference in ED visits between the privately insured and those without any HI. We also found that near-older adults without any HI were significantly less likely to have had an overnight hospital stay than those with any type of HI.…”
Section: Discussioncontrasting
confidence: 99%
“…Controlling for sociodemographic and health statuses, those who lacked HI were seven times more likely to have postponed or foregone needed healthcare due to cost, and only 15% to 23% as likely to have had contact with any healthcare professional in the preceding 12 months. We also found that the uninsured aged 50-64 were less likely to have visited an ED than those with public HI; however, in contrast to an aforementioned earlier study finding [22], we found no difference in ED visits between the privately insured and those without any HI. We also found that near-older adults without any HI were significantly less likely to have had an overnight hospital stay than those with any type of HI.…”
Section: Discussioncontrasting
confidence: 99%
“…These variables are balanced across black and non-black doctor treatment.15 We also asked a question about usual source of care in the baseline survey, but many subjects selected multiple options making their responses difficult to interpret. As inZhou et al (2017), we find that the uninsured use the ER at a similar rate to the insured, though they have fewer total hospital admissions and doctor visits. Results available on request.…”
mentioning
confidence: 53%
“…The higher prevalence of medical care delay or avoidance among respondents with health insurance versus those without insurance might reflect differences in medical care-seeking behaviors. Before the pandemic, persons without insurance sought medical care much less frequently than did those with insurance ( 10 ), resulting in fewer opportunities for medical care delay or avoidance.…”
Section: Discussionmentioning
confidence: 99%